Saberes e práticas dos professores de história sobre a cultura pomerana - Santos, Clóvis Mariano dos (2025)
This research aims to understand and explore, through the narratives of history teachers from the municipal public network of Santa Maria de Jetibá/ES, the knowledge they mobilize to address Pomeranian culture in the classroom. It also seeks to understand the motivating factors that led the Pomeranians to leave their homeland, as well as the historical context of their arrival and settlement in Brazilian lands. The study aims to identify the knowledge mobilized by history teachers to enhance Pomeranian culture and its connection to identity construction. Additionally, it seeks to identify, in the narratives of Pomeranian immigrant subjects, their memories regarding their culture in public and private spaces, alongside the production of a documentary about Pomeranian culture in school contexts. To achieve our research objectives, we base our study on the theoretical and methodological premises of Oral History through the works of Meihy and Passos (1996), Alberti (2004), and Portelli (2010). In discussing professional knowledge, we engage with Tardif (2014), Tardiff and Lassard (2012), and Monteiro (2007). We also analyze identity issues based on the studies of Bauman (2005), Hall (2006), and Silva (2014)